The prevalence of oral anticoagulation in patients with atrial fibrillation in Portugal : systematic review and meta-analysis of observational studies - Caldeira, Daniel (2014)
© 2014 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. All rights reserved.